Research on innovative design of a new rope knotter - Yanmei Meng; Hao Chen; Yuan Liang; Johnny Qin; Qinchuan Zhao; Jin Wei (Advances in Mechanical Engineering, 2019)
Aiming at the complex structure and high manufacturing process requirements of traditional knotter, this article proposes a new rope knotting method. Based on the knotting method, a knotter is designed to use a new mechanism which is made up of two new incomplete gear mechanisms to drive rope clamping mechanism and rope hooking and griping mechanism. First, a kinematic cycle diagram of the knotter is determined, and the structures of each key mechanism are designed. Then, a virtual prototype of the knotter is established by Unigraphics and imported into Automated Dynamic Analysis of Mechanical Systems to analyze the kinematic of each key mechanism. The success rate is 98.4% through 500 physical tests on the physical model of the knotter. The results indicate that the knotting method is reliable. The knotter can meet the requirements of structure, posture, and coordination during knotting process. The new knotter has no separate mechanism for cutting rope and tripping out of the rope buckle. Therefore, the structure is simplified and reduces the design and manufacturing difficulties. Furthermore, the new incomplete gear mechanism solves the problem that in the conventional incomplete gear mechanism, the driven gear can swing at a large angle or even cannot be locked in the case when the locking arc of the passive gear is too short.